Effect of storage temperature at 7Â°C on the physical-chemical and microbiological quality of industrialized cooked chicken breast meat (Acta Scientiarum. Technology, 2014)
The effect of storage temperature at 7Â°Con the physical-chemical and microbiological quality of industrialized cooked chicken breast meat was analyzed. Frozen cooked breast meat supplied from a poultry-processing industry was used. Fillets were stored at a prescribed temperature (7Â°C) for 15-17 days and the sample´s chemical composition and initial pH was determined. Color, texture and microbiology were analyzed to determine the shelf-life of the cooked chicken breast meat. Salmonella spp. and Escherichia coli were not detected. The highest values of Chroma a* were observed at 312 and 360 hours, exhibiting an intense red color resulting from meat deterioration. Chroma b* failed to show any significant difference between the first and last day of storage. Lightness (L*) was decreased with storage time and revealed a darker color caused by microbial spoilage. Texture decreased from 2.93 to 1.12 kgf. It may be concluded that shelf-life attended to expectations with regard to texture, color and microbiology of cooked chicken breast meat stored at7Â°C during 13 days.Â